Analysis of Urban Expansion and Land Use and Land Cover Dynamics of Ado-Ekiti Local Government of Ekiti State, Nigeria - Ogunlade, Idowu Adewale; Olatunji , Abiodun Johnson; Adegboyega , Emmanuel Rotimi; Reinhard Oni, Abiodun (SPC Journal of Social Sciences, 2024)
This study examined the pattern of Land Use and Land Cover Change (LULCC) in Ado-Ekiti being the only town and headquarters of Ado-Ekiti Local Government as well as the capital of Ekiti State, Nigeria for thirty-six years between 1985 and 2021 using Remote Sensing and Geographical Information System techniques covering four epochs. Seven Land Use and Land Cover (LULC) classes including Agricultural Land (AL), Barren Land (BL), Built Up Area (BU), Forest Land (FL), Range Land (RL), Water Body (WB) and Wet Land (WL) were identified in Ado-Ekiti Local Government based on USGS/Anderson’s classification model. Landsat 5 TM, Landsat 7 ETM+ and Landsat 8 OLI and TIRS images were acquired for the supervised digital image classification using Arc GIS 10.8, ENVI 8.3 and DIVA GIS software. The results obtained showed that between1985 to 2021 Built Up Area (BU) increased by about 80.98%, that is, by about five times. There was decline in Forest Land (FL), Water Body (WB) and Wet Land (WL) but increase in Agricultural Land (AL), Barren Land (BL) and Range Land (RL). After the presentation of the results, recommendations were made on the need for continuous collection, analysis, interpretation and updating of data in the study area to monitor developments in order to aid quick response in decision making by appropriate authorities.